Reconstruction of Contextual Tafsir in the Perspective of Islamic Sociology on Contemporary Social Issues - Halikul Saleh; Sugeng Wanto; Agusman Damanik (Civiliza Publishing, 2026)
Contextual interpretation of the Qur’an has become increasingly important in responding to modern social dynamics influenced by digitalization, globalization, and changing patterns of human behavior. This study aims to develop a framework of contextual tafsir applicable to contemporary social issues, particularly social media ethics, tolerance, and social justice. The research employs a qualitative method using a thematic (maudhu‘i) interpretation approach and content analysis of primary sources (the Qur’an, classical and contemporary tafsir literature) as well as secondary sources (academic journals and books). The findings indicate a significant difference between traditional textual interpretation and modern contextual interpretation, resulting in a contextual tafsir model that integrates sociological dimensions of Muslim behavioral change. This study contributes to Islamic sociology by highlighting the role of tafsir in social transformation. This qualitative research is based on a comprehensive literature review. It applies thematic (maudhu‘i) tafsir as an analytical framework, enabling the identification of major themes within Qur’anic verses. The study formulates a contextual tafsir concept that integrates textual, sociological, and normative dimensions and applies it to three contemporary social issues: social media ethics, tolerance, and social justice.